POTENSI DAUN JAHE MERAH SEBAGAI BAHAN DASAR PEMBUATAN ELEKTRODA SUPERKAPASITOR - Erman Taer; Juwita Ade Putri; Novi Yanti; Apriwandi Apriwandi; Rika Taslim (Universitas Riau, 2022)
Red ginger leaf waste (Zingiber Officinale Var Rubrum) has been successfully processed as an active carbon base material for supercapacitor electrodes. The process of making carbon electrodes starts from the preparation of the original material, drying, refining, chemical activation, integrated pyrolysis and neutralization. The focus of this research is on the chemical activator ZnCl2 which is used with different concentrations of (0.1 and 0.5) M. Activated carbon powder is printed using a press to produce carbon in the form of solid coins of uniform size. The optimization of the carbon element in the sample is carried out through a pyrolysis process at high temperature with a one-stage integrated technique. Where, carbonization in the N2 gas environment is carried out starting from room temperature 30°C up to 600°C followed by physical activation until the high temperature reaches 800°C in CO2 gas environment. Characterization of activated carbon samples from red ginger leaves begins with determining the amount of shrinkage that occurs in the pyrolysis process by measuring the mass, diameter and thickness of the carbon coins. Furthermore, the electrochemical properties were tested using two methods, namely cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) in a symmetrical two-electrode system. The electrochemical characterization was carried out under the influence of an aqueous electrolyte of 1M KOH and 1M Na2SO4 at a low potential window of 0-1 V. The optimum conditions of electrochemical properties were found in the red ginger leaf activated carbon sample with a ZnCl2 activator concentration of 0.5M for the electrolyte. KOH with a specific capacitance value of 115.9 F/g. while for electrolyte Na2SO4 found in ZnCl2 activator 0.1M with a value of 72 F/g. Through these results, red ginger leaves are known to have great potential as a base material for activated carbon electrodes to improve the performance of supercapacitors.